Evaluation of Implementation of Internal Audit, Risk Management and Good Corporate Governance - Sri Dewi Anggadini; Ari Bramasto; Sari Damayanti; Sultan Miftahul (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2021)
This study aims to determine the evaluation of the implementation of internal audit, risk management and Good Corporate Governance at PT Kereta Api Indonesia in the city of Bandung.The research approach in this research is a descriptive and verification approach using primary data. The research approach in this research is a descriptive approach using primary data. The sampling technique used is nonprobability sampling with saturated sampling method. The number of study population is 17 people, the research sample used is 17 people with data sources obtained through the results of questionnaire filling. The data analysis technique used in this study was SPSS V.26.Based on the results of research conducted it can be seen that the evaluation of the implementation of internal audit, risk management and Good Corporate Governance at PT Kereta Api Indonesia in the city of Bandung is included in the excellent category, improved management and oversight functions of corporate governance so that company performance is always stable.